Oncologic imaging a multidisciplinary approach - Silverman, Paul M. (Elsevier/Saunders, 2012)
Suitable for radiologists, surgeons, medical oncologists, and radiation oncologists, this title offers guidelines for diagnosis, staging, and surveillance, equipping members of the cancer team to make the best possible use of noninvasive diagnostic tools. It provides the multidisciplinary guidance you need for optimal imaging of malignancies.